Democratic and Authoritarian Political Systems in 21st Century World Society - Stichweh, Rudolf 1951-; Moser, Evelyn 1982-; Ahlers, Anna L. 1982-; Krichewsky, Damien 1982- (transcript Verlag, 2020)
Long description: What seemed unthinkable after the end of the Cold War and the triumph of liberalism has become reality today: the democratic world society of the 21st century is threatened by illiberal and autocratic political models. The state is no longer an instrument of a dominating stratum trying to control society. It must include individuals, produce valued outputs, know the complexity of society, and accept or deny the autonomy of other specialized function-systems. The authors analyze these political systems of a functionally differentiated world society and argue that they are completely novel because they incessantly adapt to the process of functional differentiation. To this end, they define structural core characteristics of modern policy, such as the political inclusion of everyone as a reaction to individualism; the complexity of polities arising from internal differentiation; and the increasing political decision-making handed to experts and autonomous organizations
Keywords: globalization; Politics; Society; Democracy; Sociology; Knowledge; Political Sociology; Sociological Theory; Responsiveness; Internal Differentiation; Functional Autonomy; Autocracy; Autoritarismus; Demokratie; Politisches System; Aufsatzsammlung